(untitled) (Research, Society and Development, 2022)
The objective was to compare the performance of removable complete dentures made by the digital technological method with those made by conventional techniques, through a systematic review. A search was carried out in the VHL, Medline/PubMed, EMBASE and Cochrane databases, from 1991 to January 2022, supplemented by manual search. Studies with edentulous patients, who had complete removable dentures made by the digital and analog method and who had at least one of the primary outcomes (degree of satisfaction, quality of denture finish and clinical performance of the dentures) were included. The initial search resulted in 914 articles, of which only 6 studies were considered eligible for the present search. These studies reported a total of 400 complete dentures installed in 193 patients, 160 of whom had conventional dentures and 240 had digital dentures. The age of the participants ranged from 58 to 69 years, with an average follow-up time of 12 months. Regarding the performance of complete dentures, the digital complete denture presented greater advantages compared to the conventional one in relation to: the degree of patient satisfaction; to the average time of execution of complete dentures, where an increase of 3,5 hours more for conventional totals; in terms of cost, being also higher for the manufacture of conventional prostheses. Therefore, it can be concluded that the studies suggest that the performance of the digital complete denture seems to be superior in terms of patient satisfaction, reduced number of clinical sessions and lower laboratory costs when compared to conventional prostheses.